SISTEM KOMPUTERISASI DALAM MENINGKATKAN PRODUKTIVITAS KERJA PEGAWAI DI KANTOR CAMAT SIBABANGUN KABUPATEN TAPANULI TENGAH - Samsul Bahri Pane (Jurnal Ilmiah Ilmu Komunikasi Communique, 2019)
Current technological developments, encourage every organization to process data quickly, completely and accurately. One technology that can help in processing data in an organizational environment is to use computer devices and computerized systems that are good and appropriate. This research was conducted at the Sibabangun District Head Office in Central Tapanuli District, the form of research used in this study was descriptive qualitative to help analyze data and facts obtained. Based on the results of data analysis, it is known that the role of computerization in increasing employee work productivity at the Sibabangun Sub-District Head Office in Central Tapanuli Regency is very helpful for the work process carried out in the sub-district office. In addition, computers are tools that support the work processes used by the employees of the Sibabangun sub-district office to create systems and services that produce good work productivity for the sub-district.